Basalioma - Fadhila Dzakiyya; Adi Rizka (Lembaga Pengembangan Kinerja Dosen, 2024)
Basalioma, also known as basal cell carcinoma (BCC), is the most common skin malignancy found throughout the world. Basaliomas commonly occur in the elderly population, which is associated with cumulative sun exposure and other exogenous damage. Older (65–79 years) to very old (>80 years) white individuals showed the highest increase in basalioma incidence rates. In Indonesia, data from the Cancer Registration Agency in 2009 shows that skin cancer ranks 4th out of the 10 most common types of cancer. The most common location is in the nose area. The incidence of metastasis is 0.01-0.1%, and occurs lymphogenously and hematogenously. The most significant causes are exposure to ultraviolet radiation and genetic predisposition. Basaliomas tend to occur in areas of chronic sun exposure and therefore the majority, about 74%, occur on the head, face and neck. Basaliomas usually arise from the lowest layers of the epidermis, although a small number may originate from the outer root sheath of the pilosebaceous unit. The incidence of basalioma is directly proportional to age and inversely proportional to the amount of melanin pigment in the epidermis. Surgery remains the first line of treatment for this disease. Surgical modalities include electrodessication, curettage, excision, cryosurgery, and Mohs micrographic surgery..